The baby garden: islam & me - Jafri, Adeeba (Goodword Books India, 2002)
"The Baby Garden" is a heartwarming story that often centers around the themes of nurturing and growth, symbolizing the care and love given to children. It typically describes a magical garden where babies flourish, highlighting the importance of a supportive environment for development. The narrative emphasizes values such as compassion, community, and the joy that comes from watching young ones thrive, encouraging readers to appreciate the beauty of childhood and the role of love in fostering growth.